Novel Strategies for the Improvement of Stem Cells’ Transplantation in Degenerative Retinal Diseases - Simona Delia Nicoară; Sergiu Șușman; Oana Tudoran; Otilia Bărbos; Gabriela Cherecheș; Simion Aștilean; Monica Potara; Olga Sorițău (Stem Cells International)
Currently, there is no cure for the permanent vision loss caused by degenerative retinal diseases. One of the novel therapeutic strategies aims at the development of stem cells (SCs) based neuroprotective and regenerative medicine. The main sources of SCs for the treatment of retinal diseases are the embryo, the bone marrow, the region of neuronal genesis, and the eye. The success of transplantation depends on the origin of cells, the route of administration, the local microenvironment, and the proper combinative formula of growth factors. The feasibility of SCs based therapies for degenerative retinal diseases was proved in the preclinical setting. However, their translation into the clinical realm is limited by various factors: the immunogenicity of the cells, the stability of the cell phenotype, the predilection of SCs to form tumors in situ, the abnormality of the microenvironment, and the association of a synaptic rewiring. To improve SCs based therapies, nanotechnology offers a smart delivery system for biomolecules, such as growth factors for SCs implantation and differentiation into retinal progenitors. This review explores the main advances in the field of retinal transplantology and applications of nanotechnology in the treatment of retinal diseases, discusses the challenges, and suggests new therapeutic approaches in retinal transplantation.